Dynamic solutions of non-uniform extensional motions as applied to instability of fibre-forming processes - Zahorski, S. (Archives of Mechanics, 1998)
The concept of non-uniform extensional motion of materially non-uniform simple, locally isotropic materials is applied to the case of dynamic solutions of fibre-forming processes. The approach presented enables discussion of instability problems taking into account inertia as well as shearing effects. It is shown that small stationary disturbances may lead to unstable situations while small oscillatory disturbances grow limitlessly only for certain discrete frequencies. Some comparisons with previous results are made.